A miniaturized directional antenna for microwave breast imaging applications. Issue 10 (25th September 2017) - Mahmud, Md Zulfiker; Islam, Mohammad Tariqul; Rahman, Md Naimur; Alam, Touhidul; Samsuzzaman, Md
Abstract : A novel compact directional antenna with improved gain is proposed for microwave breast imaging (MBI) applications. The radiating fins are modified by etching several slots to make the antenna compact and enhance antenna performance in terms of bandwidth, gain, efficiency, and directivity. Several parameters are studied and optimized to frequency from 3.1 to 6.5 GHz, which is typically used in the breast imaging system. The electrical length of the antenna is 0.39λ × 0.46λ × 0.01λ at the lower frequency band. The result shows that the antenna exhibits −10 dB impedance bandwidth of 4.3 GHz (2.7–7 GHz) with directional radiation pattern. The peak gain of the proposed prototype is 7.8 dBi and fractional bandwidth is 92%. The time domain results show that the fidelity factor for face to face is 0.92 and for side by side is 0.62, which prove the directivity and lower distortion of the signal. The proposed prototype is successfully simulated, fabricated, and measured.